The Effectiveness of The Discovery Learning Model Using Discussion Method Compared to Lecture Method on Students’ Learning Outcomes in English Subject on Job Application Letter Material - Qurrotul Uyun; Kamilia Putri; Arisandi Setiyawan; Raziqah; Slamet (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effectiveness of the Discovery Learning model through discussion and lecture approaches in improving students' English learning outcomes on job application letters. The study used a quasi-experimental method with a pre-test and post-test control group design involving two grades of 12 at SMA Negeri 3 Pamekasan, each consisting of 27 students. Data collection was carried out using a learning outcome test that had been tested for validity and reliability to measure students' abilities before and after treatment. Data analysis was carried out using the SPSS program through a normality test to determine data distribution, a homogeneity test to test the equality of variance between groups, and an independent sample t-test to determine differences in learning outcomes between the discussion group and the lecture group. The results showed that the data met the assumptions of normality and homogeneity. In addition, there were significant differences in student learning outcomes, where the group using the discussion approach achieved higher results than the lecture group. These findings indicate that interactive and student-centered learning is more effective in improving students' English comprehension and learning outcomes